EFEKTIVITAS HUKUM PENGGUNAAN CCTV SEBAGAI ALAT BUKTI DALAM PENEGAKAN HUKUM TINDAK PIDANA PENCURIAN DI KOTA GORONTALO - Verencia Pricilia Ponto; Kindom Makkulawuzar; Haritsa, Haritsa (Unisan Law Review, 2024)
This research aims to (1) evaluate the legal effectiveness of using Closed Circuit Television (CCTV) as evidence in combating theft crimes in Gorontalo City within the framework of Criminal Procedure Law. (2) Identify challenges associated with the use of CCTV recordings as evidence in the law enforcement of theft crimes in Gorontalo City, specifically in relation to Criminal Procedure Law provisions. Employing a normative-empirical research approach, the study utilizes literature review and field studies for data collection. Findings reveal that (1) CCTV's effectiveness in law enforcement against theft crimes in Gorontalo City serves a crucial role as investigative guidance and court evidence. During investigations, CCTV aids in perpetrator identification and evidence collection. In court, CCTV recordings offer a clear depiction of criminal events, reinforcing the case. (2) Main challenges in using CCTV as evidence in theft crime law enforcement stem from two factors. First, potential poor quality of CCTV images may hinder event identification, complicating investigations if recordings miss crucial details due to internal or external factors. Second, inadequate maintenance of CCTV facilities poses obstacles in perpetrator identification. Addressing these factors is crucial for effective law enforcement against theft crimes. The research recommends improving CCTV installations to leverage recordings as investigative leads. Residents of Gorontalo City are urged to install CCTV in vulnerable areas for prevention and identification of theft activities. Clarity in laws governing the use of CCTV as evidence is essential, and involvement of digital forensic experts is recommended to enhance effectiveness and reliability in investigations and court proceedings.